Nakba and Survival The Story of Palestinians Who Remained in Haifa and the Galilee, 1948-1956 - Manna, Adel (University of California Press, 2022)
Beginning in 1948, Israeli paramilitary forces began violently displacing Palestinian Arabs from Palestine. Nakba and Survival tells the stories of Palestinians in Haifa and the Galilee during, and in the decade after, mass dispossession. Manna uses oral histories and Palestinian and Israeli archives, diaries, and memoirs to meticulously reconstruct the social history of the Palestinians who remained and returned to become Israeli citizens. This book focuses in particular on the Galilee, using the story of Manna's own family and their village Majd al-Krum after the establishment of Israel to shed light on the cruelties faced by survivors of the military regime. While scholars of the Palestinian national movement have often studied Palestinian resistance to Israel as related to the armed struggle and the cultural struggle against the Jewish state, Manna shows that remaining in Israel under the brutality of occupation and fighting to return to Palestinian communities after displacement are acts of heroism in their own right. "Nakba and Survival is bound to be the standard authoritative study of the 1948 war in the city of Haifa and the Galilee."-Salim Tamari, coauthor of Camera Palaestina: Photography and Displaced Histories of Palestine "Essential reading for anyone wishing to understand how the events of 1948 continue to shape the Palestinian condition today."-Maha Nassar, author of Brothers Apart: Palestinian Citizens of Israel and the Arab World "The empathy for, and solidarity with, Adel Manna's historical subjects shapes the book's narratives, the questions it asks, and its deft use of oral histories. A must-read for all those who want to understand daily lives under settler colonial rule."-Orit Bashkin, coeditor of Jews and Journeys: Travel and the Performance of Jewish Identity